Pentamyrmexini, a new tribe for Pentamyrmex spinosus, a remarkable new genus and species of Pentatomidae (Hemiptera: Heteroptera) from Thailand - Rider, David A.; Brailovsky, Harry (Zootaxa, 2014)
Pentamyrmex spinosus new genus, new species is described, and a new tribe is erected for this remarkable insect. This is the first report of ant mimicry in the Pentatomidae.